Pengaruh Inquiry Based Learning Terhadap Keterampilan Sosial Anak - Febru Puji Astuti, Febru Puji Astuti; Mutiara, Diajeng Puspa; Madyawati, Lilis (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2023)
This study aims to determine the effect of the Inquiry Based Learning (IBL) learning method on early childhood social skills in group B BA 'Aisyiyah Meduro students, Mungkid District, Magelang Regency. This research was carried out using an experimental design with the type of One Group Pretest-Posttest Design by taking initial measurements and final measurements. The subjects of this study were group B students of BA 'Aisyiyah Meduro, Mungkid District, Magelang Regency for the 2021/2022 academic year, totaling 14 students. The sampling technique in this study used purposive sampling. The data collection method was carried out using the observation method which was measured using an observation sheet based on indicators. The analysis technique used is a non-parametric statistical test with the Wilcoxon Signed Ranks Test with the help of the computer program SPSS for windows version 21. The results showed that the Inquiry Based Learning (IBL) learning method had an effect on early childhood skills. This is evidenced by the results of the Wilcoxon signed ranks test Z count of -3.300b with Asymp.Sig (2-tailed) is 0.001 with an average comparison of the initial measurement value of 30.64 and the final measurement of 56.64 after being given Treatment using Inquiry Based Learning learning method. The results of the study can be said that activities using the Inquiry Based Learning learning method affect the social skills of early childhood.